HarvestPlus Bangladesh Bio-fortified Rice Project: Baseline Dietary Survey - International Food Policy Research Institute; University of California, Davis; International Centre for Diarrhoeal Disease Research, Bangladesh (International Food Policy Research Institute, 2019)
A multi-stage cluster survey was conducted in two rural rice-producing regions in Bangladesh in 2007-2008 as the initial project of a HarvestPlus multi-stage research program to determine the potential impact of zinc-biofortified rice on the zinc and health status among children in Bangladesh who are at risk of zinc deficiency. In each region, 240 children ages 24-48 months were enrolled. Dietary information was collected primarily by direct observation and weighing of food preparation and consumption, including test weighing of milk intakes by breast-fed children. Height and weight were measured in all children, and in a subset of children, blood samples were collected and analyzed for concentrations of serum zinc and indicators of infection.